Single-cell transcriptomics reveals mechanisms of Galt gene editing–induced liver injury involving HGF–VEGF–mediated intercellular signaling in mice - Li, Zhihao; Wang, Ning; Ruan, Haolong; Li, Qi; Zhang, Xingling; Liu, Nian; Li, Yong; Gu, Lantao; Yue, Pengpeng; Yu, Honghao (Frontiers in Cell and Developmental Biology, 2026)
Galactosemia, a genetic disorder caused by mutations in the human GALT gene, often leads to multi-organ damage, with liver injury being particularly prominent. To elucidate the molecular mechanisms of Galt in liver injury, this study employed the CRISPR/Cas9 system to construct a Galt (c.847 + 1G > T) gene-edited mouse (GAL mouse) model. Quantitative Real-time PCR and Western blotting revealed a significant reduction of Galt gene in GAL mice. Elevated liver index, serum ALT and AST levels, and H&E staining results indicated significant hepatocyte edema in GAL mice, suggesting a pronounced liver injury phenotype. Single-cell transcriptomics further unveiled significant changes in hepatocyte subtype proportions, with downregulation of metabolism-related genes and upregulation of immune-related genes. Cell communication analysis demonstrated that the communication of HGF and VEGF signaling pathways was significantly enhanced following Galt gene editing. The enhancement of HGF and VEGF signaling pathways may lead to hepatocyte edema, thereby causing liver injury. The GAL mouse model constructed in this study not only revealed the crucial roles of the Galt gene in liver metabolism, immune regulation, and cell communication, but also provided new insights into the pathogenesis of galactosemia and potential therapeutic targets.